Orientalist Influence and Its Decline in Indonesian Islamic Studies: Tracing Intellectual and Institutional Transformations - Suaidi; Hilmy, Masdar; Al Asyari, Haekal (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
It is undeniable that many Orientalist works have hurt Oriental images up to the present time. However, it is equally important to acknowledge the positive contributions of Orientalist scholarship to the advancement of Oriental studies. In the context of Indonesian Islamic studies, both Western researchers (Orientalists) and Indonesian-born Muslim scholars have played a significant role in shaping Islamic educational institutions and influencing individual Muslim scholars. In terms of higher education institutions, all traditional State Islamic institutions (IAINs) and most of the State Islamic Colleges (STAINs) have been transformed into Islamic State Universities. At the individual level, a substantial number of Indonesian-born scholars—many of whom studied under Orientalists in Western universities—have emerged as influential figures, making significant contributions to the development of both Islamic and general academic fields in Indonesia. However, over the past decade or so, such influence has notably declined. By utilizing data from individual initiative research and employing ‘loose’ text and contextual analysis methods, this article examines the early progress and recent decline of Orientalist influence on Indonesian Islamic studies, and discusses potential future trajectories.